Effect of Benzene Exposure on Ferritin and Complete Blood Count in OiLibya420 Gas Station Workers (British Journal of Multidisciplinary and Advanced Studies, 2024)
Benzene is a colorless liquid that easily evaporates in the air and can lead to negative impacts on the workers’ health. Also, it can cause cancer. This study aimed to evaluate the effect of benzene on the ferritin level and blood of workers in petrol station.This study has a cross sectional design. It includes 32 participants out of which 16 are exposed workers and 16 non exposed ones. The data was collected by using a questionnaire about socio-demographic characteristics and symptoms of benzene exposure. Also, Blood samples were taken to test ferritin and complete blood counts and analyzed by using Statistical Package for Social Sciences. The results of the study revealed that exposure to benzene in some workers leads to decreasing serum ferritin, MCV, MXD and MCH, and increased WBC, RBC, and HCT. There was a statistical difference in the WBC, RBC, MCV, MCH, LYM, and MXD between the exposed and non-exposed groups. There was a positive relationship between years of experience and effects of benzene on WBC, and a clear correlation between the exposed workers’ age, HGB and ferritin levels. Benzene has negative impacts on the health of workers, which dictates the necessity of worker wearing personal protective equipment in the workplace.